2022
DOI: 10.1038/s41598-022-07037-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neural epidermal growth factor-like 1- and exostosin 1/exostosin 2-associated membranous nephropathy: a single-center retrospective study in Japan

Abstract: Membranous nephropathy (MN) is the leading cause of nephrotic syndrome in adults. We previously reported that the prevalence of phospholipase A2 receptor (PLA2R)- and thrombospondin type 1 domain containing 7A (THSD7A)-associated MN patients in Japan is 52.7% and 9.1%, respectively. In addition to PLA2R and THSD7A, we assessed the presence of newly discovered target antigens, neural epidermal growth factor-like 1 (NELL-1), semaphorin 3B (SEMA3B), and exostosin 1/exostosin 2 (Ext1/Ext2), in renal specimens from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Recently, the deposition of EXT1/EXT2 in LMN glomeruli have been validated in a few studies [2][3][4][5][6] . We confirmed that a subset of LMN patients was positive for EXT1/EXT2 in a Chinese cohort and the ratios of EXT-positive among combined and pure LMN were similar to studies by Ravindran et al and Saïdi et al 2,4 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…Recently, the deposition of EXT1/EXT2 in LMN glomeruli have been validated in a few studies [2][3][4][5][6] . We confirmed that a subset of LMN patients was positive for EXT1/EXT2 in a Chinese cohort and the ratios of EXT-positive among combined and pure LMN were similar to studies by Ravindran et al and Saïdi et al 2,4 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…NELL1 in primary MN: Most cases of NELL1 MN do not have an underlying associated disease [ 8 , 15 , 16 ]. In these cases, the kidney biopsy does not show any secondary features (although IgG1 might be the dominant IgG subtype), but importantly, there is no underlying disease association.…”
mentioning
confidence: 99%
“…The frequency of PLA2R-associated MN among primary MN cases in Japan was reported to be about 53%, which is considerably less frequent than in Europe, US, or China 16,17 . The frequency of PLA2R-associated MN in our MN cohort was slightly lower than the previously reported frequency of PLA2R-associated MN in primary MN cases in Japan.…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge, no association between rheumatic diseases or BUC use and NELL1-associated MN has been reported, which led us to plan the next RA-MN cohort. It should be added that there was a recent report from Japan that 2 out of 4 patients with NELL1-associated MN were RA patients 17 .…”
Section: Discussionmentioning
confidence: 99%